Balancing nature and faith: protection and conservation of water resources from the perspective of islamic law - Abu Bakar, Syatirah; Abdullah@Abd Halim, Mohd Zulhelmey; Roslim, Salmah (Universiti Teknologi MARA, Kedah, 2025)
Water is indispensable to life, a resource critical for the survival of all living beings and the sustenance of ecosystems. In Islam, water holds both practical and spiritual importance, regarded as a blessing from God and a shared trust that must be protected, conserved and equitably distributed. Rooted in the Qur’an and the teachings of the Prophet Muhammad (peace be upon him), Islamic principles emphasize water as a communal resource, its management as a collective responsibility, and its preservation as a moral obligation.